New insights from data analysis of 12 global clinical studies on hair shedding - Yingjie Li; Shengnan Lin; Sarah Paterson; Tony Dadd; Jiayin Gu; Ranjit K. Bhogal; Zulfa Hudaya; Hepsy Y. Selliah; Mingming Pu; Jianing N. Sun (International Journal of Cosmetic Science, 2026)
Abstract Excessive hair shedding continues to be a major concern for individuals, negatively affecting their wellbeing and confidence. This research analysed 12 clinical studies involving 805 participants (323 males and 482 females) across eight countries (China, Indonesia, UK, India, Brazil, Thailand, Turkey and US) with concerns about hair loss. Two recent studies in China and a study in Indonesia were investigated in depth, focusing on hair shedding and breakage conditions, and age‐related differences in hair shedding. The two China studies were further investigated in hair shedding during different scalp or hair care procedures (washing, drying, and combing after drying). Additionally, nine historical clinical studies from various regions were further reviewed for hair shedding and breakage conditions to provide a global view on this topic. Across the three recent Asian studies, whilst total hair fall comprised both shed hairs from the root (exogen hairs with a typical club end) and broken hairs, shed hairs from the root represented the predominant proportion, accounting for an average of 96.5% of total hair fall in Chinese female participants, 98.8% in Chinese male participants, and 72.2% in Indonesian female participants. Analysis of the nine historical studies supported the insight that shed hairs from the root are more than broken hairs. Regardless of region or gender, more shed hairs from the root were collected from scalp than broken hairs, with shed hair proportions ranging from 67.1% to 97.7%. Data mining of the two recent Chinese studies revealed that most hair shedding occurred during the washing stage (49.6% in females and 74.1% in males), followed by drying and combing after drying. Further analysis of the 2 recent Chinese studies and the recent Indonesian study also explored the differences in hair shedding with age. Spearman correlation analysis showed an increasing trend of hair shedding with age in female participants. Subgroup analysis of younger (18–42 years) and older participants (>42 years) using the Mann–Whitney U test also indicated increased hair shedding with age in females.